Understanding teachers’ job satisfaction through work-life balance policies / Farah Shazlin Johari... [et al.] - Johari, Farah Shazlin; Ruslani, Muhammad Ridzuan; Rasli Samudin, Nor Maslia; Mohd Zolkapli, Nurhafizah; Basirun, Siti Norashikin (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Work-life balance play an important role in influencing employee’s quality of social and working life together with job satisfaction in the organization. Nowadays, teachers are also included in the context of work-life balance due to academic workload and career issues. In this study, researchers aim to explore work-life balance policies that influence teacher’s job satisfaction in selected Malaysia boarding school. Only 56 school teachers were selected to represent as respondents consist of teachers from language, mathematics, science, social science, counselling unit, and vice principals department. The questionnaires were distributed using convenience sampling. The elements of work-life balance policies such as flexibility policies, welfare policies, job design and leave provisions were included in this study to examine potential influence on teacher’s job satisfaction. Based on statistical analysis using SPSS, Pearson Correlation analysis four elements of work-life balance policies indicated positive and significant relationship with job satisfaction, with flexibility policies showed the strongest relationship toward teacher’s job satisfaction. Most of teachers in selected Malaysian boarding school also demonstrated high level of job satisfaction at the workplace.